PEMBERDAYAAN MASYARAKAT DESA TUNGGULO MELALUI INOVASI PUPUK CAIR FERMENTASI BERBASIS LIMBAH IKAN DAN KULIT PISANG KEPOK - Muh. Alsere Bardian Sahaba; Rieny Sulistijowati S; Wila Rumina Nento; Hamidah Manteu; Indriati Husain (Jurnal Abdi Insani, 2026)
Indonesian farmers still largely depend on chemical fertilizers, which in the long term can reduce soil quality and increase agricultural production costs. In Tunggulo Village, Tilongkabila District, Bone Bolango Regency, the use of organic waste such as fish waste and banana peels is still very limited and is generally only discarded. However, this waste contains nutrients that can be used as raw materials for making liquid organic fertilizer through a fermentation process. Therefore, community empowerment activities are needed to increase knowledge and skills in processing organic waste into environmentally friendly and economically valuable liquid fertilizer. This community service activity used a pre-test and post-test design to measure changes in participants' knowledge before and after training. The activity was carried out in three main stages, namely preparation, counseling, and training in the production of fermented liquid fertilizer based on fish waste and kepok banana peels. A total of 20 participants who were members of farmer groups were actively involved in the activities. The results of the activities showed an increase in participants' understanding after attending the counseling and training. The average pre-test score of 7.70% shows that participants' initial knowledge of fermented liquid fertilizer was still very low, while the post-test score increased to 81.83% after the activity was carried out. This increase shows that demonstration-based extension and training methods are effective in improving community knowledge and skills. Participants were also able to practice the process of making liquid fertilizer independently and showed interest in developing production on a household scale. This activity not only increased community awareness of organic waste management but also opened up opportunities for the development of sustainable agriculture-based village businesses.